The Impact of the Intranatal Edu Application on Skills for Assisting in Childbirth - Sulastini Sulastini; Rosita Alvia; Wieda Widyatry Qarragyta (Postgraduate, University of Mataram, 2023)
It is necessary to change teaching strategies and media because of the persistently poor pass rate of students' laboratory abilities in intranatal procedures. One such strategy is the use of engaging, interactive, and entertaining learning materials, such as Android applications. The goal of developing the app Intranatal Edu was to help students become more proficient. This study aims to evaluate the impact of the Intranatal Edu Application on the birth control knowledge of nursing students. Quantitative experimental research with a single group pre- and post-testing is the kind of research being done here. With a sample size of 60 respondents, the population of this study consisted of enrolled students in the third semester of the undergraduate nursing study program. Because the p-value of 0.005 is less than the significance threshold of 0.05, the Wilcoxon H0 test findings can be disregarded. It can be inferred that there is a difference in the birth support skills scores in Stage II pre- and post-test. According to this study, using the Edu Intranatal Application can effectively improve students' skills